The Actual Tasks of Development of Dialogism of Students - Jermolajeva, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper deals with one of the fast developing modern educational approaches – the pedagogy of dialogue. The structure of main dialogical skills elaborated by the author makes it possible to concretize the tasks of dialogical education. The main dialogical skills (which are at the same time the main preconditions of dialogical interaction) are: a) the skill of dialogical attitude; b) the skill of antinomian thinking, c) open-mindedness and creativity. An effective dialogue teaching requires a clear comprehension of the dialogismorientated/non-dialogism-orientated views, statements and reactions of students. In this paper the materials of cross-cultural research are used, which was carried out in Riga and Moscow schools in 2010-2011. The gained results allowed assessing the results of the dialogical development of students from Form 9 to Form 12 (Form 11), to observe the problem points and to establish more precisely the pedagogical tasks and directions for dialogical upbringing